PEMAHAMAN SAK EMKM, SOSIALISASI LAPORAN KEUANGAN DAN PENERAPAN SAK EMKM DENGAN MODERASI UKURAN USAHA - Vianastasia Adryant; Maria Rio Rita (Jurusan Akuntansi Fakultas Ekonomi Universitas Siliwangi, 2020)
The purpose of this study was to determine the effect of understanding SAK EMKM, socialization of financial statements in implementing SAK EMKM with business size as a moderating variable. This research is motivated by the phenomenon of the application of SAK EMKM by SMEs which is still limited due to the lack of knowledge and understanding of these rules and their benefits for businesses. Primary data were obtained through surveys of MSME owners in the Salatiga food and beverage sector in 4 (four) sub-districts in Salatiga including Sidorejo, Argomulyo, Tingkir and Sidomukti sub-districtswho have received socialization on financial reports. The data is then processed using a moderated regression analysis (MRA). The results of this study prove that 1.) SAK EMKM understanding has a positive effect on the application of SAK EMKM; 2.) the socialization of financial statements has a significant positive effect on the application of SAK EMKM; 3.) business size does not moderate the understanding of SAK EMKM on the application of SAK EMKM.